The Trials and Tribulations of Structure Assisted Design of KCa Channel Activators - Shim, Heesung; Brown, Brandon M.; Singh, Latika; Singh, Vikrant; Fettinger, James C.; Yarov-Yarovoy, Vladimir; Wulff, Heike (Frontiers in Pharmacology, 2019)
Calcium-activated K+ channels constitute attractive targets for the treatment of neurological and cardiovascular diseases. To explain why certain 2-aminobenzothiazole/oxazole-type KCa activators (SKAs) are KCa3.1 selective we previously generated homology models of the C-terminal calmodulin-binding domain (CaM-BD) of KCa3.1 and KCa2.3 in complex with CaM using Rosetta modeling software. We here attempted to employ this atomistic level understanding of KCa activator binding to switch selectivity around and design KCa2.2 selective activators as potential anticonvulsants. In this structure-based drug design approach we used RosettaLigand docking and carefully compared the binding poses of various SKA compounds in the KCa2.2 and KCa3.1 CaM-BD/CaM interface pocket. Based on differences between residues in the KCa2.2 and KCa.3.1 models we virtually designed 168 new SKA compounds. The compounds that were predicted to be both potent and KCa2.2 selective were synthesized, and their activity and selectivity tested by manual or automated electrophysiology. However, we failed to identify any KCa2.2 selective compounds. Based on the full-length KCa3.1 structure it was recently demonstrated that the C-terminal crystal dimer was an artefact and suggested that the “real” binding pocket for the KCa activators is located at the S4-S5 linker. We here confirmed this structural hypothesis through mutagenesis and now offer a new, corrected binding site model for the SKA-type KCa channel activators. SKA-111 (5-methylnaphtho[1,2-d]thiazol-2-amine) is binding in the interface between the CaM N-lobe and the S4-S5 linker where it makes van der Waals contacts with S181 and L185 in the S45A helix of KCa3.1.